Comparison of Bleaching Products With Up to 6% and With More Than 6% Hydrogen Peroxide: Whitening Efficacy Using BI and WID and Side Effects – An in vitro Study - Lilaj, Bledar; Dauti, Rinet; Agis, Hermann; Schmid-Schwap, Martina; Franz, Alexander; Kanz, Fabian; Moritz, Andreas; Schedle, Andreas; Cvikl, Barbara (Frontiers in Physiology, 2019)
The aim of this study was to evaluate the effect of bleaching agents containing different concentrations of hydrogen peroxide (HP) on color-change and on enamel-surface in bovine teeth. Furthermore the influence on cell viability and proliferation was investigated. 240 teeth were randomly assigned into four groups, (home bleaching ≤ 6%, in-office bleaching ≤ 6%, in-office bleaching > 6% HP and control group). Bleaching was performed after artificial staining and the bleached index BI as well as the whiteness index WID was measured at several time points. Chemical analysis for HP concentrations and the pH of the bleaching products was done. Furthermore, enamel surfaces of randomly selected specimens were analyzed using scanning electron microscopy (SEM) and cytotoxicity of the tested bleaching products was evaluated in vitro using dental pulp cells and L929 cells. A statistically significant whitening effect was observed in almost all products. As expected all investigated products resulted in decreased cell viability, however with different values of LC50 (median lethal concentration). SEM analysis showed an analogue of enamel alterations with decreasing pH, increasing exposure time, and increasing HP concentration. Bleaching agents containing a low HP concentration are considered to be effective and to have less damaging effects on enamel and tested cells.